Single identity in check-in using NFC in airport - Mikhael Bagus Renardi; Noor Cholis Basjaruddin; Kuspriyanto Kuspriyanto (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
An increase in transactions in airports is in line with a growing number of airline passengers, thus, a system which can enhance the service may be required. One of the concerns related to airline services is the long time for transactions due to the time required for each transaction and the number of transactions for each passenger. One of the transactions which require long time is the check-in process. In addition, the conventional check-in process also requires paper which its use is rapidly rising due to the increasing number of passengers. Hence, an NFC (Near Field Communication)-based system can be applied to accelerate transactions and to reduce the use of paper. Transactions in airports require several documents including booking reference and passengers’ identity cards, and both of which can be digitally stored in an NFC device. This study revealed that the implementation of SI could accommodate the check-in process in airports and decrease the redudancy of passenger data.